Export Diversification and Economic Growth of ECOWAS Member States - Olure-Bank, Adeyinka Michael; Mustapha, Muktar; Zakaree, Saheed; Abraham, Alexander; Yakubu, Alfa (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: Using the data of export diversification index which is excluded in previous studies and most the pervious only look at the relationship between ED and GDP, excluding per capita income as basics for development. Again, previous studies results are contradictory on impact of export diversification performance. Additionally, this paper provides robust empirical evidence of a positive effect of export diversification on per capita income growth.Research Objectives: This paper has the objective to examines how export diversification (ED) increase economic growth and per capita income.Research Methods: The paper achieve its objectives using, panel least technique and co-integration test are used on time series data of 1984-2022 for ECOWAS states.Empirical Results: The paper shows that the export diversification index has a significant influence on GDP growth but inverse, however, manufacturing value-added shows weak but a positive influence on the growth per capita income. Again, the paper reveals that high skewness of ECOWAS region to primary products export which could be responsible for the low growth per capita income. The finding of this is not the volume of exported products that matters, but how dynamic is exported products.Implications: The paper therefore recommends ECOWAS countries need to develop processing capability for export that comes from endogenous sufficiency.JEL Classification: C23, F10, O47, O55